2009
DOI: 10.1097/icl.0b013e3181b5003b
|View full text |Cite
|
Sign up to set email alerts
|

Early Symptomatic Presbyopes—What Correction Modality Works Best?

Abstract: For this group of early presbyopes, the AIR OPTIX AQUA MULTIFOCAL--Low Add provided a successful option for visual correction, which was supported by the results of subjective ratings, many of which were made during or immediately after performing such activities as reading, using a computer, watching television, and driving. These results suggest that making a prediction of "success or not" based on consulting room acuity tests alone is probably unwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 14 publications
2
30
2
Order By: Relevance
“…The objective results with AOMF concur with other studies assessing center-near lenses for HCVA,12, 16, 17, 18, 19, 20, 21 LCVA,18, 21 and CS12, 16, 17, 19 at 6 m and stereopsis at 40 cm 17, 18, 20. However, many of these studies also reported better results with AOMF for HCVA at 40 cm 12, 17, 18, 19, 20, 21.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The objective results with AOMF concur with other studies assessing center-near lenses for HCVA,12, 16, 17, 18, 19, 20, 21 LCVA,18, 21 and CS12, 16, 17, 19 at 6 m and stereopsis at 40 cm 17, 18, 20. However, many of these studies also reported better results with AOMF for HCVA at 40 cm 12, 17, 18, 19, 20, 21.…”
Section: Discussionsupporting
confidence: 87%
“…However, simultaneously focused and defocused retinal images can lead to decreased quality of vision,1, 12, 13 decreased contrast sensitivity13, 14 and ghosting 13, 15. Despite these limitations, good visual outcomes have been reported with some center-near designs12, 16, 17, 18, 19, 20, 21 with some studies reporting similar12, 19 or better12, 16 outcomes compared to a zonal-refractive multifocal. However, these limitations also indicate improvements in multifocal designs are needed to service the current and future presbyopic CL market.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, considerably lower rates of stereopsis were achieved with multifocal designs in this study than those reported for the same designs in previous studies (21-54 seconds of arc) (15,19) , even when considering only the mild presbyopia group in this study. We believe that this discrepancy may attributable to the inclusion of a wider age range of patients with presbyopia in this study who fell into the mild presbyopia group and the different evaluation methods used.…”
Section: Discussioncontrasting
confidence: 54%
“…Ferrer-Blasco et al (13) found 22.40 ± 8.23, 56.40 ± 18.00, and 54.80 ± 20.23 sec of arc in 25 patients fitted with Proclear multifocal lenses from Cooper Vision using the Howard-Dolman, Titmus, and Random Dot sterereotests, respectively. Previous studies have analyzed NSA in patients fitted with different models of multifocal contact lenses with the same (12,22) or different stereotests (5,21,(23)(24)(25) . Considering all these previous studies, there has been some variability among results.…”
Section: Discussionmentioning
confidence: 99%